O performatywach i generowaniu - Brożek, Anna; Kasprzyk, Zuzanna (Filozofia Nauki, 2007)
The conception of performative utterances proposed by John Langshaw Austin is unclear and provokes many fundamental questions. We compare this proposal with Jacek Juliusz Jadacki's conception of performatives, being much more precise one. We develop Jadacki's intuitions and propose to characterize performatives as expressions fulfilling a specific semantic function: A type-expression W is a performative generating an intentional state of affairs S iff there is a convention K and circumstances C such that the convention K says: if somebody utters a token-expression W in circumstances C, so the state of affairs S will take place. Subsequently, we analyze the problem of correctness of performative utterances and relations between different criteria of correctness of performative acts. On the basis of these analyses, the paradox of annulled marriage is formulated and the problem of perfomatives in law is sketched.